Prevalence of Appendicular Perforation among Patients Undergoing Emergency Appendectomy at a Tertiary Care Hospital (Nepal Medical College Journal, 2025)
Appendicitis is a common cause of abdominal pain, and misdiagnosis or delayed diagnosis of acute appendicitis leads to perforation, postoperative complications, and an increased length of hospital stay. A retrospective study was performed at the Department of Surgery, Nepal Medical College Teaching Hospital, Gokarneshwor Municipality-8, Kathmandu, from Jan 2020 to Dec 2022, involving 235 patients who fulfilled the inclusion criteria. In our 3-year study, 235 patients (139 males and 96 females) underwent emergency appendectomy. Pain was present in all patients, with a mean duration of 24.89 ± 6.835 hours and a WBC ranging from 9,600 to 18,400 cells/mm3. The average luminal diameter was 9.362 ± 1.3 mm. A total of 22 patients (9.4%) had a perforated appendix. Perforation was more common among males. Similarly, perforated patients presented with pain for 24.5 ± 7.7 hours and a WBC of 15,454 ± 1818.044 cells/mm3. Imaging revealed the luminal diameter of 10.7 ± 1.069 mm. The prevalence of perforation among patients with appendicitis was relatively low with higher male-to-female ratio and a substantial portion of patients occurring in the 18-23 years age group.